Price Fraction Changes Impact on Stock Trading Indicators: An Events Study on Indonesia Stock Exchange - Adi Teguh Suprapto; Mulyono Mulyono; Danang Prihandoko (Bina Nusantara University, 2019)
This research presented differences of stock price fraction system to stock trading indicator variables such as volume, value, and frequency of stock trading transactions on companies listed in Indonesia Stock Exchange. The purpose of this research was to measure and analyze the difference of stock price fraction system to stock trading indicator variables. Sample determination based on the sampling method was saturated, i.e., the technique of determining the sample by using all members of the population as a sample. The sample in this research used JCI data as it represents the 115 issuers listed on the Indonesia Stock Exchange during the research period. This research used Mann-Whitney U Test to find out whether there were differences between two groups of data that were not related (independent) with the classification; group 1 was the volume data, the value and frequency of stock trading before the new price fraction that was applied 02 May 2016. While the second group data volume, value and frequency of stock trading after applying the new price fraction 02 May 2016. This research finds that the stock trading indicators reflected by the trading volume of stocks, the value of the stock, and the frequency of stock trading has a significant difference before and after the implementation of the new stock price fraction.